GDF-15 tecidual e sérico em neoplasias de ovário - LIMA, Cid Almeida de (2015)
INTRODUCTION: Ovarian cancer is difficult to diagnose the main cause of death among gynecological tumors. The tumor marker GDF-15, a member of the TGF-β family, is found elevated in ovarian cancer is associated with tumor invasion, lymph node metastasis and worse prognosis. Your dosage has greater sensitivity than other markers in early stages of cancer, reflecting the extent and stage of the disease. OBJECTIVE: The aims were to evaluate serum levels of GDF-15 and immunohistochemical staining of GDF-15 in patients with primary ovarian epithelial benign and malignant neoplasms. METHODS: Sixty-five patients were evaluated in the Clinic of Pelvic Mass in the Discipline of Obstetrics and Gynecology/Oncology Research Institute (IPON) of the Federal University of Triangulo Mineiro, undergoing surgery according to predetermined criteria. The patients were divided into two groups: benign ovarian neoplasms (n = 31), and primary epithelial ovarian malignancies (n = 34). Immunohistochemistry study and ELISA were performed to evaluate GDF-15 serum and tissue, respectively. Fisher exact test was used to compare the results obtained by immunohistochemistry. Serum levels of GDF-15 were expressed as mean and standard deviation, and values were compared by Student’s t-test. Values less than 0.05 were considered significant. RESULTS: Serum levels of GDF-15 were higher in malignancies than in benign neoplasms, but there was no statistical significance. GDF-15 was significantly more frequent in the stroma of malignant tumors compared with benign tumors (p = 0.0034). There is no statistical significance in epithelium evaluation. CONCLUSION: GDF-15 immunohistochemical staining is higher in the stroma of malignant epithelial ovarian cancer compared to benign tumors, indicating the importance of stromal compartment in ovarian neoplasms.